Numerical Study of Acoustic-Structure Interaction of Selected Helicoidal Resonator with Flexible Helicoidal Profile - ŁAPKA, Wojciech (Archives of Acoustics, 2018)
The paper presents the results of numerical studies of acoustic-structure interaction of selected helicoidal resonator with helicoidal profile made of an elastic material. Considered a well-recognized acoustic system for one representative type of acoustic helicoidal resonator with two resonant frequencies that correspond to previous studies of the author. Due to the large range of flexible materials to study, this work focuses on the change of material density, Poisson’s ratio and Young’s modulus as the basic parameters describing the properties of elastic materials. The results indicate a significant interaction between the acoustic attenuation performance of helicoidal resonator and elasticity of the helicoidal profile. These interactions are most evident in the frequency range in which the helicoidal resonator is revealed to be effective acoustic damper.